Mesophilic anaerobic co-digestion of sewage sludge with glycerine: Effect of solids retention time. (1st March 2018) - Zahedi, S.; Rivero, M.; Solera, R.; Perez, M.
Abstract: The main objective of this paper is to examine the effect of the increase in organic loading rates (OLRs), by reducing the solids retention time (SRT) from 20 d to 5 d, in single-phase mesophilic anaerobic co-digestion of sewage sludge with glycerine (1% v/v). It was experimentally confirmed that anaerobic co-digestion of these biowastes under steady-state conditions can achieve an 85 ± 5% reduction in volatile fatty acids (VFA) at SRTs of between 20 and 9 d, with a methane production yield of around 0.8 l CH4 /l/d. Decreases in the SRT not only allow the sludge stability and biogas production to be maintained, but also lead to an increase in the waste that could be treated and lower operating costs. Therefore, mesophilic anaerobic co-digestion of sewage sludge and glycerin at a SRT lower than 20 d is possible and preferable due to being more economical and environmentally friendly.